The role of transformational leadership on the empowerment and creativity of Administrative employees working at king Abdul-Aziz University in Saudi Arabia - Al Somali, Sabah bin Abdullah; Metwally, Razan Farid (Journal of Economic, Administrative and Legal Sciences, 2018)
Organizations can achieve their goals through their leaders who have special traits that enable them to face recent challenges and handle them efficiently. The educational institutions are considered the stone corner and the main base in establishing an educated society and they have a crucial role in transforming a nation from a developing nation to a developed one.This study aims to examine the effect of transformational leadership on empowering and influencing the creativity of administrative staff at King Abdul-Aziz University (KAU). The data were collected using online survey administered to administrative staff. The questionnaire was distributed electronically and using paper questionnaires to all administrative employees at KAU. 333 responses were received and multiple regression analysis was used to test the hypothesis of the study. The results showed a positive significant relationship between transformational leadership and employees' empowerment. Also, results showed a strong positive relationship between transformational leadership and employees’ creativity. The average analysis and the standard deviation were also used to determine transformational leadership practices at KAU. The study found that leaders are practice transformational leadership at KAU. Finally, the study set some recommendations to the educational institutions to encourage employees to be creative by developing and finding new ways to solve old problems.
Keywords: transformational leadership; empowerment; creativity; higher education institutions